KIRIM HALK OYUNLARI İLE GİRESUN HALK OYUNLARININ KARŞILAŞTIRMALI İNCELEMESİ - HAMZAÇEBİ, GÖKHAN (Fırat Üniveristesi, 2018)
Bir toplumun geçmişten geleceğe taşıdığı önemli mirasların başında kültür mirasları gelmektedir. Çalışmamızda, Karadeniz Havzası'nda göçler yolu ile bir dönem yaşam sürmüş Kırım Türkleri ile Giresun yöresi anonim halk kültür ürünlerini, halk oyunlarını, müzikal benzerliklerini ve kültürel yapılarını konu almaktadır. Çalışmamızın ilk kısmında Kırım Tarihi, Kırım Bölgesi'nden Anadolu'ya yapılan göçler ile Doğu Karadeniz Bölgesi'nden Kırım'a yapılan göçler ele alınmıştır. Kırım'da Türk kültürü, Kırım ve havalisinde dil özellikleri, atasözleri ele alınmış, anonim halk edebiyatı ürünlerinden örneklere yer verilmiş, Kırım Halk Müzikleri ve Oyunları ile Kırım Türklerinde "cırlar", "yırlar" kavramları ele alınmıştır. Tezimizin sonraki kısmında ise Karadeniz'in önemli beldelerinden biri olan Giresun'un tarihi ve kültürü hakkında bilgiler verilmiş, Kırım Halk Oyunları ile Giresun Halk Oyunları'nın karşılaştırmalı bir incelemesi yapılmış, Kırım Kaytarması ile Giresun Horonları ve Karşılamasının benzer ve farklı yönlerine temas edilmiş, Kırım ve Giresun Halk Oyunları'ndaki figürlerin benzerlikleri ve farklılıkları ile Kırım ve Giresun Müziği'nin ritim, melodi ve motif yapılarındaki benzer ve farklı yönler konu edinilmiştir.

Cultural heritages are one of the most important heritage that a society carries from the past to the future. Our study focuses on Giresun local anonymous folk culture products, folk dances and musical similarities and cultural structures of Crimean Turks who have lived for some time in the Black Sea region through migration. In the first part of the study, it has been mainly dealth with the history of Crimea, migrations to Anatolia from the Crimean region and migrations to the Crimea from the Eastern Black Sea Region. Turkish culture in Crimea, language features in Crimea and its vincinity and proverbs have been mentioned and examples of anonymous folk literature products have been included and Crimean Folk Music and Dances, and the concepts of "short poems" and "folk music" in Crimean Turks have been discussed. In the second part of our thesis, it has been given information about the history and culture of Giresun which is one of the important geographical regions of Black Sea, and it has been examined a comparative study of Crimean Folk Dances and Giresun Folk Dances, it has been touched the similar and different aspects of the Crimean "kaytarma" and Giresun region "horon" and "karşılama". Similarities and differences between the figures in the Crimean and Giresun Folk Dances and the similar and different aspects of the rhythm, melody and motif structures of Crimean and Giresun Music have been discussed.
Comparative analysis of Folk Dances With Crimean and Giresun Folk Dances
Keywords: Müzik